DIGITAL PUBLISHING COMMUNICATIONS CIRCUIT - MURRAY, PADMINI RAY; SQUIRES, CLAIRE (Knygotyra, 2014)
The publishing value chain has remained relatively consistent since the invention of the printing press. Robert Darnton’s influential model of the communications circuit of the book, which tracks how intellectual property circulated in 18th century France, has been a largely accurate representation of the publishing industry until the late 20th century. This article examines changes to the publishing industry, particularly as a result of the disruptions and disintermediations of the digital age, and proposes a re-drawing of the communications circuit for the 21st century. The research in this article was supported by the Arts and Humanities Research Council grant number AH/J01317X/1 The Book Unbound: Disruption and Disintermediation in the Digital Age.